2020
DOI: 10.1111/nicc.12541
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge and attitudes regarding physical restraint in Turkish intensive care units

Abstract: Background: Physical restraint is still widely used despite studies supporting a reduction in its use. The development of guidelines to reduce the use of PR first requires the identification of factors related to the use of alternative methods.Aim: This study aimed to determine factors associated with the use of alternatives to physical restraint (PR) in intensive care units.Design: This was a cross-sectional descriptive study.Methods: Data were collected from adult intensive care units of three hospitals in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
1
8
0
4
Order By: Relevance
“…Studies have shown that, in addition to lack of knowledge, time pressure due to a heavy workload seems to prevent consideration of alternatives to restraint and preventive measures (Ertuğrul & Özden, 2020 ; Möhler & Meyer, 2014 ). This could be one reason why preventive measures were not mentioned more often in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, in addition to lack of knowledge, time pressure due to a heavy workload seems to prevent consideration of alternatives to restraint and preventive measures (Ertuğrul & Özden, 2020 ; Möhler & Meyer, 2014 ). This could be one reason why preventive measures were not mentioned more often in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…In the somatic acute care hospital (henceforth referred to as ‘hospital’) setting, little is known about the attitudes of the nursing staff. Some studies have been conducted in the intensive care area (e.g., [ 10 , 21 , 22 , 23 ]); however, these focused more on reasons for the use of restraints (e.g., using the Perception of Restraint Use Questionnaire), on knowledge and application practices (partly using questionnaires designed for the study), or on attitudes assessed only using qualitative methods. Therefore, the aim of the current study is to assess nursing staff’s attitudes in a hospital setting using a standardised questionnaire and to identify their associations with staff characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…PR has been widely used among intensive care patients in many countries (Luke et al, 2014;Pan et al, 2018;van der Kooi et al, 2015). In the ICU, it is mainly used to restrict patient movement, reduce injuries from falling and prevent accidental catheter removals (Ertu grul & Özden, 2020;Leahy-Warren et al, 2018). However, evidence does not show that restraint can prevent accidental catheter removal (ACR) (Perren et al, 2015).…”
Section: Introductionmentioning
confidence: 99%